2007
DOI: 10.1007/s10792-007-9080-7
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic response to intravitreal triamcinolone in eyes with macular edema

Abstract: Intravitreal triamcinolone temporarily changed central retinal artery blood flow and posterior ciliary arteries' peak systolic blood velocity in eyes with retinal vein occlusion whilst no response of blood flow to triamcinolone injection but only transiently altered end diastolic blood velocity in posterior ciliary arteries was observed in diabetic eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…23 Cekiç et al demonstrated that 4 mg intravitreal triamnicolone acetonide treatment transiently altered blood flow in CRA and flow velocity in PCAs in eyes with retinal venous occlusion, whereas it has no effect on any vessel except for a transient decrease in flow velocity in PCAs in eyes of diabetics. 24 The present study is, to our knowledge, the 1 st prospective clinical trial to determine the effects of intravitreal bevacizumab therapy on ocular hemodynamic parameters in patients with neovascular AMD. In our study, we found that PSV and EDV of NPCA and PSV of TPCA were significantly lower after intravitreal bevacizumab injection (p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…23 Cekiç et al demonstrated that 4 mg intravitreal triamnicolone acetonide treatment transiently altered blood flow in CRA and flow velocity in PCAs in eyes with retinal venous occlusion, whereas it has no effect on any vessel except for a transient decrease in flow velocity in PCAs in eyes of diabetics. 24 The present study is, to our knowledge, the 1 st prospective clinical trial to determine the effects of intravitreal bevacizumab therapy on ocular hemodynamic parameters in patients with neovascular AMD. In our study, we found that PSV and EDV of NPCA and PSV of TPCA were significantly lower after intravitreal bevacizumab injection (p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Koz et al [23] found that topical anti-glaucomatous travoprost and latanoprost significantly reduced the RI in the CRA and ophthalmic artery, respectively, and topical bimatoprost had no effect on ocular hemodynamics [18][19][20][21][22][23] . Çekiç et al [24] demonstrated that 4 mg intravitreal triamnicolone acetonide treatment transiently altered blood flow in CRA and flow velocity in PCAs in eyes with retinal venous occlusion, whereas it has no effect on any vessel except for a transient decrease in flow velocity in PCAs in eyes of diabetics [19][20][21][22][23][24] .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have indicated that injection of IVT has a significant effect on ocular hemodynamics. Çekiç et al 26 observed a significant reduction in end-diastolic arterial blood velocity of posterior ciliary arteries in patients with DME 1 month after the injection of IVT. However, they reported that these changes returned to baseline values within 3 months.…”
Section: Discussionmentioning
confidence: 98%
“…25 The mechanism of action of intravitreal triamcinolone is proposed to be changes in retinal vessel diameters and perfusion regulations. [26][27][28][29][30][31] Corticosteroids are effective in DME due to their anti-inflammatory effects, by reducing VEGF levels, and their stabilization effects on the blood- retina barrier. 14 It is thought that VEGF carries out its vascular effects via nitric oxide, which is a potent vasodilator.…”
Section: Discussionmentioning
confidence: 99%